Efektivitas Penggunaan Media Leaflet Dan Metode Ceramah Terhadap Pengetahuan Ibu Hamil Tentang Diabetes Melitus Pada Kehamilan - Hilamuhu, Fendrawaty; Djunaid, Ulfiana; Zakaria, Fatmah; Abdullah, Tria Ivanca (Madu : Jurnal Kesehatan, 2024)
Diabetes mellitus pregnancy sufferers in Indonesia reaches 2.1%, while in Gorontalo Province is estimated to 0.12% and Gorontalo Regency racks first in cases of diabetes mellitus. This research was conducted in the Hunggaluwa Village. The purpose of this research was to determine the effectiveness of the use of leaflet media and lecture methods on the knowledge of pregnant women about diabetes mellitus in pregnancy in Hunggaluwa Village. This type of research is a quantitative study with a pre-experimental design. The sampling technique in this study is accidental sampling using 21 respondents. Base the results of statistical tests using the Wilcoxon test, it was found that the 0.001 <0.05 so that He was rejected and Ha was accepted, geaning that then was an effective use of leaflet media and lecture methods on the knowledge of pregnant women about diabetes mellitus in pregnancy in Hunguluwa Village.